In vitro inhibition of Pseudomonas aeruginosa adhesion by Xylitol - Sousa,Letícia Pinheiro de (2011)
This study evaluated, in vitro, the antimicrobial activity and the anti-adherent property of xylitol (0.5, 2.5 and 5.0%, w/v) on two Pseudomonas aeruginosa strains (ATCC 9027 and clinical). The assay of antimicrobial activity was performed to determine a minimum inhibitory concentration (MIC) and the adhesion test was performed, by which the parameters regarding, growth in the culture medium, number of colony forming units (CFUs) released and slide evaluation by scanning electron microscopy (SEM) were analyzed. The Statistical Package for the Social Sciences (SPSS) was employed for statistical analysis. Results showed that xylitol had no antimicrobial activity on these strains; however, the inhibition of bacterial adherence was observed in microphotographs obtained by SEM. These results indicated that xylitol could be a future alternative to combat bacterial colonization.